An Evaluation of Service Provision and Novel Strength Assessment on Patient Outcomes in a UK-Based Pulmonary Rehabilitation Setting. (3rd May 2020) - Barlow, Ruth; Jones, Ben; Rogerson, Mike; Bannister, Hannah; Stuart, Rebecca; Iqbal, Jawadh; Andrews, Leanne; Easton, Izzie
Abstract: This study's purpose was to (i) assess the impact of a 7-week pulmonary rehabilitation (PR) programme upon patient outcomes; incremental shuttle walk test (ISWT), COPD assessment tool (CAT), Clinical COPD Questionnaire (CCQ) and the Hospital Anxiety and Depression Scale (HADS); (ii) assess the impact of COPD severity on ISWT, psychological functioning and quality of life measures following PR; (iii) assess the feasibility of incorporating individually prescribed one repetition maximum (1RM) training loads into the existing strength training programme. Patients were people with COPD enrolled onto one of three versions (locations A, B and C) of a 7-week PR programme, which consisted of group exercise sessions and a social plus education element. Two locations incorporated individually prescribed training loads. Minimal clinically important changes (MCICs) are reported for the ISWT across all locations. Statistically significant changes in both CAT and the CCQ were found, with MCIC's evident for CAT score overall and individually at location B. MCIC's were not found for the CCQ. No statistically significant or MCICs were evident for the HADS. MCIC's were present only in patients with mild to moderate severity for the ISWT. For the CAT, moderate, severe and very severe patients with COPD experienced MCIC's. MCIC's and statistically significant increases in 1RM strength were seen at both locations. These findings evidence an effective PR service. Basic strength exercise programming and assessment are feasible and should be implemented in PR services to maximise patient outcomes.